Arrival by ambulance in acute heart failure: insights into the mode of presentation from Acute Studies of Nesiritide in Decompensated Heart Failure (ASCEND-HF). Issue 3 (17th March 2016) - Ezekowitz, Justin A; Podder, Mohua; Hernandez, Adrian F; Armstrong, Paul W; Starling, Randall C; O'Connor, Christopher M; Califf, Robert M
Abstract : Objectives: Limited data exist assessing the relationship between ambulance versus self-presentation and outcomes in patients with acute heart failure (AHF). Setting: Clinical trial sites in North America. Participants: 1068 patients enrolled in the Acute Studies of Nesiritide in Decompensated Heart Failure (ASCEND-HF) trial. Primary and secondary outcome measures: The association between ambulance use and dyspnoea improvement, 30-day mortality or HF rehospitalisation and 180-day mortality. Results: Of the 1068 patients in the substudy, 832 (78%) self-presented (SP) and 236 (22%) patients presented via ambulance. Patients presenting via ambulance were older, more likely to be female, have a higher ejection fraction but similar natriuretic peptide levels as patients who SP. Patients presenting by ambulance (compared with SP) trended towards more dyspnoea improvement at 6 (p=0.09) and 24 h (p=0.10). The co-primary end point (30-day mortality or HF rehospitalisation) was similar between groups (ambulance 12.2% vs SP 11.4%, p=0.74). Patients who presented by ambulance had a higher 30-day and 180-day mortality rate than those who SP (30-day: 4.3% vs 2.2%, p=0.08; 180-day: 15.1% vs 10.3%, p=0.04). After adjustment for baseline characteristics, patients arriving by ambulance (compared with SP) had a 2-fold high risk of 30-day mortality (OR 2.12, 95% CI 0.94 to 4.79), but no relationship to the composite of 30-day mortality/HF rehospitalisation (OR 1.01, 95% CI 0.63 to 1.63). Conclusions: Among patients with AHF, 30-day and 180-day mortality is 1.5–2 times higher for those with presenting via ambulance compared with patients who self-present. Understanding patient-related and system-related factors of ambulance use for patients with AHF is important. Trial registration number: NCT00475852.